2019
DOI: 10.2135/cropsci2019.04.0234
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Effects on Corn Plant Sap Flow Rates and Soil Water Dynamics

Abstract: Cover crops (CC) are used for soil quality improvement. However, the effects of CC on soil water availability for cash crop is yet inconclusive. Plant sap flow measurement techniques are among the most reliable methods to evaluate water stress and water consumption by measuring the whole‐plant transpiration. The objective of the study was to quantify plant sap flow dynamics in corn (Zea mays L.), soil water dynamics, and corn yields in response to CC and no cover crop (NCC) management. The study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The VWC of CC soil was 7, 9, and 5% greater at 10‐, 20‐, and 30‐cm depths, respectively, compared with NCC. Similarly, Rankoth, Udawatta, Gantzer, Jose, & Nelson (2019) reported 9, 8, and 4% greater VWC at the 0‐to‐10‐, 10‐to‐20‐, and 20‐to‐30‐cm depths, respectively, in CC soil compared with NCC in Mexico silt loam soil (fine, smectitic, mesic Vertic Epiaqualfs). Another study in Iowa, USA, reported 0.041 and 0.033 m 3 m −3 greater volumetric soil moisture at 10‐ and 20‐cm depths, respectively, under CC compared with NCC (Daigh et al., 2014), indicating the ability of CC soil to hold more soil water compared to NCC.…”
Section: Resultsmentioning
confidence: 85%
“…The VWC of CC soil was 7, 9, and 5% greater at 10‐, 20‐, and 30‐cm depths, respectively, compared with NCC. Similarly, Rankoth, Udawatta, Gantzer, Jose, & Nelson (2019) reported 9, 8, and 4% greater VWC at the 0‐to‐10‐, 10‐to‐20‐, and 20‐to‐30‐cm depths, respectively, in CC soil compared with NCC in Mexico silt loam soil (fine, smectitic, mesic Vertic Epiaqualfs). Another study in Iowa, USA, reported 0.041 and 0.033 m 3 m −3 greater volumetric soil moisture at 10‐ and 20‐cm depths, respectively, under CC compared with NCC (Daigh et al., 2014), indicating the ability of CC soil to hold more soil water compared to NCC.…”
Section: Resultsmentioning
confidence: 85%
“…Embraced as a volunteer cover crop itself, however, red sprangletop may be able to provide ecosystem services in regional cropping systems including organic systems. These services could include reducing high summer soil temperatures, decreasing surface water runoff and controlling erosion, sequestering carbon and nutrients in the soil, and reducing soil compaction (Blanco‐Canqui et al., 2012; Mubvumba et al., 2021; Rankoth et al., 2019; Steele et al., 2012). Sprangletop species have been reported to be palatable to livestock (Pitman & Holt, 1983) and thus could also provide an opportunity for grazing, potentially bringing added economic benefit to an organic system.…”
Section: Discussionmentioning
confidence: 99%
“…increased soil porosity and these changes in pore size distribution are reflected in significant increases in transmission pores. Additionally, Rankoth et al (2019) evaluated the effects of CC on soil moisture and sapflow of corn ( Zea mays ) with and without CC and found that, at 10, 20 and 30 cm depths, CC plots had 14%, 12% and 4%, respectively, greater soil water content compared with NCC plots. These authors concluded that plots under CC management maintained greater soil moisture conditions and provided more moisture to the commodity crops for a longer period compared with NCC plots.…”
Section: Introductionmentioning
confidence: 99%